2011
DOI: 10.1177/0009922811417293
|View full text |Cite
|
Sign up to set email alerts
|

Increased Documentation and Management of Pediatric Obesity Following Implementation of an EMR Upgrade and Education

Abstract: We found an increase in documentation and management of overweight children following an EMR upgrade that calculates BMI percentiles for age and gender. Physician education was an important adjunct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…The availability of reminders or alerts may prompt actions to promote healthy lifestyle behaviours in the outpatient setting. 9,17 However, our results show that even in severely obese children (Z 3), a diagnosis was not registered in 66.1% of cases, suggesting that use of a more sensible anthropometric tool is not enough, and additional medical education is needed to increase the detection of overweight and obesity. By contrast, when the diagnosis was registered, most of the patients were referred to specialists.…”
Section: Implications Of the Findingsmentioning
confidence: 71%
See 2 more Smart Citations
“…The availability of reminders or alerts may prompt actions to promote healthy lifestyle behaviours in the outpatient setting. 9,17 However, our results show that even in severely obese children (Z 3), a diagnosis was not registered in 66.1% of cases, suggesting that use of a more sensible anthropometric tool is not enough, and additional medical education is needed to increase the detection of overweight and obesity. By contrast, when the diagnosis was registered, most of the patients were referred to specialists.…”
Section: Implications Of the Findingsmentioning
confidence: 71%
“…Our findings not only show us that there is low awareness of the obesity burden among physicians, but also that further actions need to be taken in order to promote full use of the EHR's capabilities because recent studies have shown that use of EHR to facilitate the identification of nutritional status can help in the management of obesity in children, enhancing the quality of care provided when compared with not using an EHR. 17,18 The EHR used at HIBA is the only way physicians have to register events on patients under their care in the outpatient setting. Our EHR is patient-centred and problem-oriented; physicians enter terms into specific domains (problem list, procedures, discharge summary, etc.)…”
Section: Implications Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] Physician and staff training in these programs also involves education and awareness of the AAP guidelines, screening techniques, and counseling strategies. [21][22][23][24][25] Similarly, interventions involving the use of electronic medical records (EMRs) have proven successful in improving guideline adherence in physicians treating pediatric overweight and obesity. [25][26][27][28] The PDPH clinics are in the process of implementing an EMR system, which could further improve processes of care for all children.…”
Section: Discussionmentioning
confidence: 99%
“…The use of such medical records has been found to increase the diagnosis and counseling of overweight children. 30 Childhood overweight and obesity are more prevalent among racial minorities 1 ; however, evidence on lifestyle counseling differences by race remains limited and inconclusive. In a study of preventive obesity counseling in healthy weight children, non-Hispanic patients received more counseling than Hispanics.…”
Section: Discussionmentioning
confidence: 99%